Green Winged Accountant: Makassar Version of the "Pappasang Tu Riolo" Cultural Approach - Mustamin, Mustamin; Lucyani, Lucyani; Tenripada, Tenripada; Betty, Betty; Husnul, Husnul (International Journal Papier Public Review, 2020)
This study aims to explore how the role of an accountant who migrates to interpret and apply the Makassar version of the Pappasang Tu Riolo values. The research was motivated by the presence of nomads with an educational background of accountants who came from the Makassar tribe which researchers called Green Winged Accountants with the cultural approach of Pappasang Tu Riolo. The approach used in this research uses interviewing techniques that cannot be separated from the eight codes of ethics for accountants in Indonesia. The findings of this study, when linked with the Makassar version of the accountant's code of ethics and culture of Pappasang Tu Riolo, have three main points, namely, first, responsibility to God, meaning that everything that is done must be done based on his orders and stay away from prohibitions. Second, accountability to others ensures that they do not differentiate as social beings who are still in a productive work and cultural order, but must maintain harmony and dignity in society. Third, responsibility to oneself, which means ensuring that every time someone does a job, he fulfills his obligations or keeps a predetermined commitment.